Exergames in Individuals with Down Syndrome: A Performance Comparison Between Children and Adolescents - Macias, Adrian; Caro, Karina; Castro, Luis A.; Sierra, Veronica; Ahumada, Edgar A.; Encinas, Iván A. (Smart Objects and Technologies for Social Good, 2018)
Individuals with Down Syndrome (DS) have delays in the development of motor function associated with impairments including difficulty with precise movements of limbs, poor balance, and poor visual-motor coordination. It has been reported that children and adolescents with DS might present differences in terms of visual-motor coordination skills, task persistence, emotional expressions, among others. Exergames have the potential to support motor coordination as they combine physical exercise with gaming technology. However, little has been said about the game experience of individuals with DS playing exergames. This work presents the results of an exploratory study of 10 individuals with DS playing a commercial exergame. Our results show a significant difference between children and adolescents in terms of task-efficacy, selective attention, and prompts. Finally, we discuss our results and the implications for designing exergames to support motor coordination of people with DS.